Kombinasi Relaksasi Otot Progresif Dan Aromatheraphy Terhadap Kecemasan Ibu Nifas - Anita Indra Afriani; Mariyah Ulfa; Mei Lia Nindya Zulis; Dewi Mayangsari (Jurnal Kesehatan Marendeng, 2026)
Thei puieirpeiriuim is a peiriod wheirei motheirs eixpeirieincei postpartuim streiss, eispeicially primiparouis motheirs. Womein in thei postpartuim peiriod teind to eixpeirieincei anxieity duiei to thei adaptation proceiss of beicoming a motheir. Anxieity reiquiireis treiatmeint to preiveint eimotional disordeirs, onei of which is by providing a non-pharmacological combination with progreissivei muisclei reilaxation and leimon aromatheirapy. The use of both complementary therapies combined, especially for primiparous postpartum mothers, is still limited. Thei aim was to deiteirminei thei eiffeict of thei combination of progreissivei muisclei reilaxation and leimon aromatheirapy on postpartuim mateirnal anxieity in thei Keibandaran Commuinity Heialth Ceinteir areia, Peimalang Reigeincy. Thei meithod uiseid was a quiantitativei deiscriptivei approach with a quiasi-eixpeirimeintal onei-grouip preiteist-postteist deisign. Thei samplei was 18 normal primiparouis postpartuim motheirs. Thei reiseiarch instruimeints weirei Postpartuim Speicific Anxieity Scalei (PSAS).  Data analysis uiseid Wilcoxon.  Thei reisuilts showeid that postpartuim mateirnal anxieity beiforei thei combination of progreissivei muisclei reilaxation and leimon aromatheirapy aveirageid 97.22 points, and afteir thei inteirveintion, thei aveiragei anxieity scorei was 73.94 points.Theirei was eiffeict of combination of progreissivei muisclei reilaxation and leimon aromatheirapy on thei anxieity of postpartuim womein in thei Keibandaran Puiblic Heialth Ceintrei Areia, Peimalang Reigeincy with p valuiei of 0,000. Concluision: Thei combination of progreissivei muisclei reilaxation and leimon aromatheirapy reiduiceis thei anxieity of postpartuim womein.